Pengabdian Kepada Masyarakat Uji Kompetensi Siswa-siswi Bidang Keahlian Teknik Kendaraan Ringan di SMK Rigomasi Bontang - Ratnawati Ratnawati (Jurnal Pengabdian Ahmad Yani, 2021)
The Expertise Competency Test (UKK) aims to measure the achievement of student competence at a certain level according to the competence of skills taken during the learning period in SMK. UKK is implemented by education units in the form of practical exams that test aspects of knowledge, skills, and attitudes. UKK is implemented using standards set by industry, Professional Certification Institutions, and/or test kits issued by the Ministry of Education and Culture. The education unit that organizes UKK must be declared eligible as a place for professional competence testing. As in the previous year, UKK scores will be calculated as school exam scores for vocational competency subjects. The UKK toolkit issued by the Ministry of Education and Culture is open and test takers can practice using the exam tool before the exam. In general, the Expertise Competency Test consists of: (1) Vocational Practice Questions (SPK) in the form of assignments for test participants to create or process and work on a product/service; (2) Practice Question Assessment Guidelines (PPSP) are instruments used to score each assessment component, competency achievement, and assessment criteria/rubric, assessment sub-component, competency achievement, and assessment criteria/rubric; and (3) the Verification Instrument for the Operator of the Vocational Practice Exam (InV) is an instrument used to assess the feasibility of an educational unit or other institution as a place to administer the Vocational Practice exam. Verification Instrument contains standard requirements for main equipment, standard supporting requirements, standard requirements for place or room and contains standard requirements for testers consisting of External examiners